Effects of chlorinated Pd precursors and preparation methods on properties and activity of Pd/TiO2 catalysts. Issue 68 (12th November 2020) - Kim, Ye Eun; Byun, Mi Yeon; Lee, Kwan-Young; Lee, Man Sig
Abstract : We investigated the effects of Pd precursors and preparation methods on the physicochemical properties and performance of Pd/TiO2 catalysts in the photocatalytic degradation of methyl violet. Abstract : We investigated the effects of Pd precursors and preparation methods on the physicochemical properties and performance of Pd/TiO2 catalysts in the photocatalytic degradation of methyl violet. To confirm the influence of the precursors, Pd/TiO2 catalysts were prepared via chemical reduction (CR) using four different Pd precursors. Additionally, to determine the effects of preparation methods, Pd/TiO2 catalysts were fabricated using K2 PdCl4 precursor via three different methods: CR, deposition–precipitation (DP), and impregnation. The CO chemisorption results showed that the catalyst prepared via DP using the K2 PdCl4 precursor, i.e., Pd/TiO2 _K_ DP, displayed the highest Pd dispersion of 12.42% owing to the stable formation of Pd(OH)2, which strongly interacted with the –OH groups on the TiO2 support. Although the catalyst prepared via CR using the Pd(NH3 )4 Cl2 ·H2 O (PA) precursor, i.e., Pd/TiO2 _PA_ CR, had the lowest Pd dispersion of 0.7%, it exhibited the highest absorption of 26% after 30 min in the dark. It was found that high Pd 2+ /Pd 0 ratio in dark conditions adversely affected the absorption of MV owing to electrostatic repulsion between the cationic dyes and metal nanoparticles. However, the Pd dispersion and the specific surface area played a key role in the photocatalytic activity under UV irradiation. Pd/TiO2 _K_ CR with higher Pd dispersion showed the highest photocatalytic activity and reaction rate of 0.0212 min −1 .